Changes in sediment greenhouse gases production dynamics in an estuarine wetland following invasion by Spartina alterniflora - Jiang, Yongcan; Shao, Yinlong; Huang, Jiafang; Du, Yunling; Wen, Yu; Tang, Hong; Xu, Jianming; Gao, Dengzhou; Lin, Xianbiao; Sun, Dongyao (Frontiers in Microbiology, 2024)
Invasive Spartina alterniflora (S. alterniflora) has significant impacts on sediment biogeochemical cycling in the tidal wetlands of estuaries and coasts.However, the impact of exotic Spartina alterniflora invasion on greenhouse gases (GHGs) production dynamics in sediments remain limited. Here, we investigated the dynamics of sediment physicochemical properties, GHGs production rates, and microbial gene abundances in a native Cyperus malacensis habitat and three invasive S. alterniflora habitats (6-, 10-, and 14-year) in the Minjiang River Estuary, China.The methane (CH 4 ), carbon dioxide (CO 2 ), and nitrous oxide (N 2 O) production rates varied both spatially and seasonally, while microbial gene abundances (bacterial and fungal gene abundances) and organic matter (TOC and TN) only varied spatially.GHGs production rates were also characterized by higher values in surface sediment (0-10 cm) compared to subsurface sediment (10-20 cm) and by seasonal variations with higher values in summer than in winter. S. alterniflora invasion can significantly increase CH 4 and CO 2 production rates, organic matter, and microbial gene abundances (p < 0.05). Temperature, organic matter and microbial gene abundances were the most dominating factor controlling the spatio-temporal variations of CH 4 and CO 2 production rates. Overall, our findings highlighted the significant role of S. alterniflora invasion in regulating GHGs production rates in coastal wetland sediments and provided fundamental data for estimating GHGs emissions and carbon sequestration in the complex tidal wetlands.